2020
DOI: 10.1177/0956462419890761
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of late presentation to care and advanced HIV in newly HIV diagnosed subjects in the Republic of Panama: 2012–2017

Abstract: Most of the information on clinical factors related to HIV infection is focused on key populations and young people. Therefore, there is little information on clinical factors related to HIV infection in older persons (>45 years old). In this study, data on CD4 lymphocyte counts were analyzed on adults who are linked to care and have their first CD4 cell count done from different regions of the Republic of Panama from 2012 to 2017. Samples were grouped according to late presentation status, region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…Besides, psychological factors, such as stigma, are more common in older people, which may also impede access to health services including HIV testing. Different from some studies ( 12 , 18 , 27 ), we did not observe any impact of gender.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Besides, psychological factors, such as stigma, are more common in older people, which may also impede access to health services including HIV testing. Different from some studies ( 12 , 18 , 27 ), we did not observe any impact of gender.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, high percentages of late presentation were shown over the time, with more than half each year. It is higher than that in some countries of Europe (14, [19][20][21][22], Australia (17), and the United States (23), lower than that in Panama (18), South Africa (24,25), Ethiopia (26), and Guangxi of China (12), and similar to that in Iran (27). It is important to notice that higher percentages of late presentation were indicated among people over 40 years old, retirees, farmers, married, heterosexuals, and people registered in Suzhou in our study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Age distribution of patients (median [IQR]: 31 years [26−39]) in this study was consistent with the latest national HIV/AIDS statistics which showed that patients with HIV/AIDS were diagnosed at a slightly younger age (one‐third between 25 and 34 years) in Turkey than in Europe (median: 33 [27−41]) 41,42 . Age at diagnosis >30 years was an independent determinant of both late presentation and presentation with advanced disease in line with other studies reporting an association between older age (lower limits varying between 20 and 45) and late presentation 15–28 . Contrastingly, a study from Sudan reported that younger people were more likely to present late 31 …”
Section: Discussionsupporting
confidence: 89%
“…However, like many studies including the analysis of the large EuResist database (1981−2019 data), which included approximately 90 000 patients from seven European countries sex was not a factor for late presentation 17–23 . Contrastingly, several studies from various geographies reported an association between male sex and late presentation to HIV/AIDS care 24–29 . There were also few studies where female sex a factor for late presentation was to care 30,31 .…”
Section: Discussionmentioning
confidence: 99%